"I don't think there is any particular music which is a direct model for what I do": Interview with Ellery Eskelin - Dely, Carole; Eskelin, Ellery (Sens public)

(untitled) (Département des littératures de langue française, 2010)
Born in 1959 in the States, the composer and tenor saxophonist Ellery Eskelin settled in New York in the early 80's. Gifted with expressiveness and resourcefulness like no-one else, his lyrical and eruptive style has made him an important figure on the world jazz scene. He has recorded dozens of albums with different formations, and regularly tours Europe. How did he become a musician? how does he work and conceive jazz? How does he create his music in collaboration with the other musicians? In this interview with Carole Dely for Sens Public, Ellery Eskelin give us some answers.